2023
DOI: 10.1111/ajag.13192
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions on feeding difficulties among people with dementia: A systematic review and meta‐analysis

Abstract: Objectives This systematic review and meta‐analysis aimed to examine non‐pharmacological interventions for helping people with dementia who experience feeding difficulties in order to improve their nutritional status. Methods The articles were searched using PsycINFO, Medline, PubMed, CINAHL and Cochrane. Two independent investigators critically appraised eligible studies. The PRISMA guidelines and checklist were used. The possibility of risk of bias was assessed using a tool to assess the quality of randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…Eating, considered the late-loss BADL, correlated with two additional geriatric syndromes-dysphagia and unintentional weight loss-alongside previously discussed issues like fecal incontinence and cognitive impairment. The current scientific literature consistently identifies dementia, unintentional weight loss, and dysphagia as key factors associated with limitations to eating [49,50]. A cross-sectional study found similar associated factors and provided two interpretations that point in distinct directions: one suggesting that those with self-feeding limitations experience inadequate nutritional care leading to malnutrition, and the other proposing that self-feeding limitations in residents may indicate a precursor of approaching the end of life [51].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Eating, considered the late-loss BADL, correlated with two additional geriatric syndromes-dysphagia and unintentional weight loss-alongside previously discussed issues like fecal incontinence and cognitive impairment. The current scientific literature consistently identifies dementia, unintentional weight loss, and dysphagia as key factors associated with limitations to eating [49,50]. A cross-sectional study found similar associated factors and provided two interpretations that point in distinct directions: one suggesting that those with self-feeding limitations experience inadequate nutritional care leading to malnutrition, and the other proposing that self-feeding limitations in residents may indicate a precursor of approaching the end of life [51].…”
Section: Discussionmentioning
confidence: 91%
“…A cross-sectional study on self-feeding did not identify NH-level explanatory variables, but suggested latent variables within the NH cluster might influence outcomes [51]. Nevertheless, NHs with kitchens have the potential to address individual factors influencing residents' eating behaviors and food choices, including innate and learned food preferences, motivations, attitudes, hunger, personality traits, and values, among other considerations [50,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation